ENHANCING STUDENTS’ ACADEMIC WRITING THROUGH ONLINE PORTFOLIO ASSESSMENT: A SELF-REGULATED LEARNING APPROACH IN DISTANCE EDUCATION - Milawati; Nuraziza Aliah; Maya Puspitasari; Suparti; Ummi Rasyidah (University of Kuningan, 2025)
This study addresses the challenges faced by students in open and distance education when writing academic papers. Despite the potential of portfolio assessment (PA) to promote reflective and process-oriented learning, teachers often encounter barriers such as heavy workloads, a lack of assessment literacy, and difficulties in designing innovative tools. These constraints prevent students from effectively engaging in selfregulated learning (SRL). This research aims to develop an online portfolio assessment tool that enhances students’ SRL in academic writing courses. Employing a Research and Development (R&D) approach adapted from Yalden’s (1987) Language Program Development model, the study involved four phases: needs analysis, design and development, validation, and evaluation. Data was collected from 61 students during the evaluation phase, providing feedback on the e-portfolio implementation. Furthermore, data was also collected from two experts who served as validators during the product validation phase. Findings indicate that the online portfolio assessment fosters students’ SRL by visualizing progress, enabling interactive feedback, and bridging synchronous and asynchronous learning gaps. The tool strengthens students’ ability to plan, monitor, and evaluate their learning, thus promoting autonomy and writing competence. The study recommends institutional integration of e-portfolio systems into distance education curricula to sustain students’ reflective learning practices.